2020
DOI: 10.1111/1475-6773.13258
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for the burden and redistribution of health care costs: Who uses care and who pays for it

Abstract: Objective To measure the burden of financing health care costs and quantify redistribution among population groups. Data Sources A synthetic population using data combined from multiple sources, including the Survey of Income and Program Participation (SIPP), Medical Expenditure Panel Survey (MEPS), Kaiser Family Foundation (KFF)/Health Research Educational Trust (HRET) Employer Health Benefits Survey, American Community Survey (ACS), and National Health Expenditure Accounts (NHEA). Study Design We estimate tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…1 The continued use of these services creates health and cost burdens for patients and society. 2 The COVID-19 pandemic interrupted some lowvalue services (along with high-value care), but paths to sustaining these lower rates remain unclear. 3 This is partly because low-value care has largely been measured and reported at the national or regional level, limiting accountability and actionability.…”
mentioning
confidence: 99%
“…1 The continued use of these services creates health and cost burdens for patients and society. 2 The COVID-19 pandemic interrupted some lowvalue services (along with high-value care), but paths to sustaining these lower rates remain unclear. 3 This is partly because low-value care has largely been measured and reported at the national or regional level, limiting accountability and actionability.…”
mentioning
confidence: 99%
“…Total health care payments, including premiums paid by workers and their employers, taxes paid, and out-of-pocket spending, consumed 33.9% of income for the poorest fifth of the population, but only 16% for the wealthiest fifth. 9 A new NPR/Robert Wood Johnson Foundation/ Harvard School of Public Health survey has found that even wealthy Americans sometimes have difficulty affording care. Among the wealthiest 1% of adults (those with household incomes above $500,000), 5% reported a serious problem paying medical bills within the past few years, 5% had a serious problem paying for prescription drugs, and 7% reported a serious problem getting health care when needed.…”
Section: Access To Care and Medical Costsmentioning
confidence: 99%
“…Survey data has also been used to examine the distributional effects of health care cost sharing and health insurance schemes, e.g. by microsimulation and other quantitative methods [33][34][35][36][37]. In a Canadian study, household expenditure survey data and quasi-experimental design were used to examine the distributional effects of introduced prescription medicine subsidy programs [38].…”
Section: Introductionmentioning
confidence: 99%